Supervision in counseling service based on psychological test result to student’s learning satisfaction - Yuzarion, Yuzarion; Alfaiz, Alfaiz; Kardo, Rici; Dianto, Mori (Universitas Negeri Padang, 2018)
As a profession, guidance and counseling have a supervision procedure in order to maintain and evaluate purpose to make evaluatif decision in guidance and counseling service. A supervision it self not only about process and result of counseling service, but also an asessment using psychological test, this asessment was useful for complete an inforrmation about psychological competence and individual difference of student. This result of psychological tes will benefit for counselor and also for student to understand and clarification about decision making in counseling service and placement for student according their expertise. A phenomena in Indonesia about counseling profession has been found that was lack of supervision process in guidance and counseling service and also lack of interest about psychology test in school, there are, it’s just to preserve an administration and formality. Phenomena in that practical way maybe can be assumed that because there is lack of information about the ideal of supervision process and also lack of experience and knowledge also untrained a supervisor and counselor about their own abilities. In this case, this paper will describe how should be a supervision be conducted, and the result of this evaluaton study show that with psychological test for student has a significant satisfaction almost 74% with their placement in first grade at senior high school.